Diseño de un sistema de gestión de calidad en base a las ISO 9001-2008 en la Florícola Agrinag s.a. ubicada en la provincia de Cotopaxi, cantón Latacunga, parroquia José Guango bajo, en el periodo del 1 de enero al 31 de diciembre del 2013 - Chuquitarco Guisha, Diana Patricia (2015)
This project trade about the design of a quality management system based in ISO 9001-2008 standards, because the company needs this design in order to have better quality control, which may respond the customer´s requirements , organization and improve overall performance. The main objective of this job is to analyze the company current situation and through this design the quality management system, demonstrating that through the its development, the company will allow to improve its competitiveness. The design of a quality management system aims to improve efficiency through excellent organization and control and through this to achieve a high degree of customer´s satisfaction and improved of company procedures based on a documented system .